PEMISAHAN DAN ANALISIS 137Cs DALAM LARUTAN ELEMEN BAKAR UJI U3Si2/Al DENSITAS 4,8 gU/cm3 DENGAN BURNUP 60% MENGGUNAKAN METODE PENUKAR KATION - Yanlinastuti; Nugroho, Arif; Br. Ginting, Aslina; Noviarty; Boybul; Haryati, Iis; amaludin, Agus; Noerpitasari, Erlina; Kriswarini, Rosika (Urania: Jurnal Ilmiah Daur Bahan Bakar Nuklir, 2023)
Separation and analysis of cesium isotope in U3Si2/Al fuel with a density of 4.8 gU/cm3 and 60% burnup by cation exchange using Lampung zeolite and Dowex resin has been carried out. The purpose of this research was to determine the weight of 137Cs in the fuel. The U3Si2/Al fuel pieces by the Bottom (B), Middle (M) and Top (T) sections were dissolved in duplicate with 6 M HCl and 6 M HNO3 to obtain a U3Si2/Al fuel solution. The separation of 137Cs started with the measurement 50 μL of fuel solution in 2 mL of 0.1 M HNO3 with a gamma spectrometer to determine the initial weight of 137Cs. The solution was put into a column containing Lampung zeolite and then flowed at a speed of 0.3 mL/minute. The resulting 137Cs isotope was bound to the zeolite and effluent containing other fission isotopes. Dowex resin, Cs carrier, and HCl was added into fuel solution, then put into a column containing R-Cl- resin. The effluent that left the column was put back into the column containing the R-NH4+ resin. The 137Cs isotope that was bound to R-NH4+ resin was eluted using 1 M HCI, then the 137Cs isotope was measured using a gamma spectrometer. The results of the 137Cs isotope measurement shows the weight of each sample with code B1=0.1772 μg/g; B-2=0.1635 μg/g; M-1=0.1395 μg/g; T-1=0.1230 μg/g and T-2=0.1036 μg/g with a recovery of B-1=99.54%; B-2=98.98%; M-1=98.99%; T-1=99.38% and T-2=98.98%. Meanwhile, the average weight of the 137Cs isotope separated by Dowex resin was B-1=0.1575 μg/g; B-2=0.1470 μg/g; M-1=0.1263 μg/g; T-1=0.1140 μg/g and T-2=0.0952 μg/g with a recovery of B-1=94.80%; B-2=95.35%; M1=97.94%; T-1=98.15% and T-2=98.89%. It was concluded that the method for separating 137Cs isotopes in U3Si2/Al fuel solution by using Lampung zeolite and Dowex resin did not have a significant difference. Both methods can be used to separate 137Cs in nuclear fuel. This analysis is used to complement the data to calculate the burnup value.